A Retrospective Analysis of Invasive Fungal Diseases (IFD) of the Central Nervous System in Children With Lymphoid Malignancies. Issue 4 (May 2020) - Ramanathan, Subramaniam; Kate, Shruti; Kembhavi, Seema; Cheriyalinkal Parambil, Badira; K. C., Anand; Bhat, Vasudeva; Prasad, Maya; Moiyadi, Aliasgar; Biswas, Sanjay; Narula, Gaurav; Banavali, Shripad
Abstract : Background: Outcomes of childhood hematolymphoid malignancies have improved several fold because of immunosuppressive chemotherapy and broad-spectrum antibiotics for managing febrile neutropenia. An apparent trade-off has been an increase in invasive fungal disease (IFD), affecting multiple organs. We report the diagnostic and therapeutic challenges in 8 children with lymphoid cancers who developed intracranial (IC) fungal abscesses between 2010 and 2017. Methods: Children below 15 years of age undergoing treatment for leukemia/lymphoma with clinicoradiologic and microbiologic evidence of IC fungal abscess were included. Demographic details, clinical profile, and management were retrospectively audited. Treatment was guided by European Organization for Research and Treatment of Cancer/Mycoses Study Group (EORTC/MSG) definitions for IFD with therapeutic drug monitoring (TDM)-directed azole dosing, and surgical intervention. Results: Eight patients (4 B-cell acute lymphoblastic leukemia, 2 relapsed B-cell acute lymphoblastic leukemia, and 2 non-Hodgkin lymphoma) were eligible for analysis. Proven, probable, and possible IFDs were seen in 2 (25%), 4 (50%), and 2 (25%) patients, respectively. Proven IFDs were invasive mucormycosis with remaining having mold infections. Cerebrospinal fluid galactomannan was positive in all 4 patients in whom it was tested. TDM was possible in 5/8 (63%) patients. Antifungal therapy was given for a median period of 4.2 months with 5 (63%) patients having complete resolution. Three (37%) patients expired, of which 2 were attributable to IFDs. Conclusions: IC fungal abscesses in children can cause significant morbidity and mortality in children with hematolymphoid cancers. Evaluation of cerebrospinal fluid galactomannan may help in early diagnosis and therapy. Prolonged antifungal therapy steered by TDM can help achieve resolution in some cases.